(untitled) (East West Medical College Journal, 2025)
Background: The perception of the people in the community about nephrotic syndrome is varied. This was not previously studied in Bangladesh. Objective: To know the Peoples’ perception about childhood nephrotic syndrome. Methods: A cross-sectional study was conducted in the inpatient department of pediatrics, Sir Salimullah Medical College & Mitford hospital for 06 months (From November 2013 to April 2014). Purposively 50 children with diagnosed case of nephrotic syndrome were included for the study. Four groups of people were interviewed, e.g. father, mother, one relative and one neighbor/attendant of adjacent bed patient. Total 200 persons were interviewed (father-50, mother-50, relatives-50 (Uncle, Aunt, Brother, Sister, Grandfather, Grandmother), neighbor-18, attendants of adjacent bed patient-32). A semi-structured questionnaire was developed for this purpose. The investigator collected data through face-to face interview in the hospital and telephonic interview from neighbors. Data were analyzed with the help of software SPSS version 16.0. Results: Among the patients, 2-6 years age group were 60.0% and 7-11 years age group were 40.0%. Seventy two percent patients were male. Among all patients 20(40%) were first attack and 30(60%) were relapse case. Among the respondents, 45.5% were within 28-37 years age, 30.5% were 18-27 years age. More than 50% respondents had idea that the disease was caused by infectious agent and other 45.5% had no idea about the cause of the disease. Perception about passing ’white element’ (albumin) in urine was significantly different between first attack and relapse cases (p=0.02). Perception about management of the disease between first attack and relapse was statistically significant (p=0.00). Perception about side effects of the drug (prednisolone) among attendants of first attack (16.7%) and relapse (83.3%) were highly significant statistically (p=0.00). Perception about complications of the disease among first attack and relapse was not statistically significant (p=0.106). Perceptions about special diet for the disease and follow-up plan of the disease among attendants of first attack and relapse were highly significant (p=0.00). Conclusion: There is lack of knowledge as to the nature of disease nephrotic syndrome, its etiology, course & prognosis of the disease. Respondents of relapse cases of nephrotic syndrome had better perception in some aspects of the disease than those of first attack. There are still information gap among the respondents which reflect that our counseling is not up to the mark. EWMCJ Vol. 13, No. 1, January 2025: 43-49